2015
DOI: 10.1016/j.jconrel.2015.09.055
|View full text |Cite
|
Sign up to set email alerts
|

Targeted endothelial nanomedicine for common acute pathological conditions

Abstract: Endothelium, a thin monolayer of specialized cells lining the lumen of blood vessels is the key regulatory interface between blood and tissues. Endothelial abnormalities are implicated in many diseases, including common acute conditions with high morbidity and mortality lacking therapy, in part because drugs and drug carriers have no natural endothelial affinity. Precise endothelial drug delivery may improve management of these conditions. Using ligands of molecules exposed to the bloodstream on the endothelia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 311 publications
(338 reference statements)
0
41
0
1
Order By: Relevance
“…Apart from the tumors, the organs exhibiting nanoparticle accumulation were the lungs and the liver, with virtually no uptake in the spleen. Although nanoparticles often accumulate in the liver and spleen, often before hepatobiliary clearance, it was previously found that the use of endothelial targets can modulate nanoparticle biodistribution to the lungs, likely due to the large endothelial component in this organ (51). …”
Section: Discussionmentioning
confidence: 99%
“…Apart from the tumors, the organs exhibiting nanoparticle accumulation were the lungs and the liver, with virtually no uptake in the spleen. Although nanoparticles often accumulate in the liver and spleen, often before hepatobiliary clearance, it was previously found that the use of endothelial targets can modulate nanoparticle biodistribution to the lungs, likely due to the large endothelial component in this organ (51). …”
Section: Discussionmentioning
confidence: 99%
“…ECs form not only the largest cellular surface area in the human body, but also a readily accessible membrane decorated with surface molecules evolved to interact with circulating blood components. 36 Like other seemingly straightforward drug delivery applications (eg, anti-neoplastic ADCs), 39,40 however, execution has proven more challenging than initially expected. Some EC surface targets, like the receptors for transferrin and insulin, are poorly suited for surface anchoring, as their biologic functions necessitate rapid internalization in response to binding.…”
Section: Discussionmentioning
confidence: 99%
“…These issues are of particular interest given substantial preclinical data suggesting the utility of anchoring biotherapeutics to endothelial surfaces. 11,14,18,19,36,46,47 Preliminary studies have mostly used monovalent scFv fusion proteins, favored based on their minimal rate of internalization and uniform molecular conformation. Examples of cargo successfully delivered via scFv fusion protein include single-chain urokinase-type plasminogen activator (scuPA), the first recombinant protein to be fused to anti-PECAM scFv.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yet, keeping in mind the huge heterogeneity of endothelial cell phenotype, one must not forget that therapy affecting endothelium should be targeted to specific vascular beds. In the last time, endothelium-targeted nanomedicine has evolved as a promising new model to deliver drugs directly into the endothelial cells [24]. Last but not least, exercise has long been appreciated as one of the most efficient measures to improve endothelial (dys)function in various ways: increasing nitric oxide (NO) bioavailability; induction of reactive oxygen species (ROS) scavenging enzymes [25]; affecting the sympathetic nervous system; and increasing the number of endothelial progenitor cells (EPCs) to list just a few.…”
Section: Endothelial Dysfunctionmentioning
confidence: 99%